Profesionalisme Guru PAI dalam Pembelajaran Berdiferensiasi pada Mata pelajaran Sejarah Kebudayaan Islam (SKI) di Madrasah Ibtidaiyah - Munawir; Rizky Lailatul Ramadhanis Sholikhah; Hapsariwa, Mega Adhelia (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This study aims to identify strategies, challenges, and solutions carried out by Islamic Religious Education teachers in implementing differentiated learning in Islamic Religious Education subjects, as well as to analyze the role of teacher professionalismin aspects of pedagogical, social, personality, and professional competence, playing a role in supporting the successful implementation of differentiated learning in Islamic Religious Education subjects. This study uses a qualitative approach with a library research method. Data collection techniques in this study were obtained from various sources which were categorized into primary sources (data obtained directly from original references) and secondary (data obtained from indirect sources) and using descriptive qualitative methods in analyzing the data. Based on the results and discussions that have been described, the professionalism of Islamic Religious Education teachers greatly influences the successful implementation of differentiated learning in Islamic Religious Education subjects in Madrasah Ibtidaiyah. Teachers who have high pedagogical, personality, social, and professional competence are able to understand the characteristics and learning needs of students individually, and are able to design appropriate learning strategies through differentiation of content, process, and product. Differentiated learning in Islamic Religious Education is important because its value and historical content demands a flexible, contextual, and enjoyable approach. Professional Islamic Religious Education teachers are not only able to manage heterogeneous classes effectively, but are also able to instill Islamic values with a humanistic and adaptive approach, so that Islamic Religious Education learning can achieve its goals optimally.